PENGUATAN NILAI RELIGIUS DAN HUMANISME DALAM KEGIATAN SANTRI PECINTA ALAM DI I’DADUL MUALLIMIN SHIGOR ISYKARIMA - faiz, wildan (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The problem of education is the first and fundamental problem in human life and life because education is the essence of human life, realizing students as humans who have religious character and humanism is the basis for assessment in the process of changing one's attitude and behavior. The formulation of the problem of this thesis is how the strengthening of humanism values in Nature Lover Students activities at I’dadul Muallimin Shighor Isy Karima, second, how the strengthening of religious values in Nature Lover Students activities at at I’dadul Muallimin Shighor Shigor Isy Karima, Third, how the role of Strengthening humanism and religious values in Nature Lover Students activities at I’dadul Muallimin Shighor Isy Karima. This study used a descriptive qualitative approach. Data collection techniques use interviews, participant observation and documentation. Data validity checking is carried out through extended participation, diligence or observability, triangulation and peer examination. The results of the study concluded that first, mukhoyomah, baksor, and takjil sharing activities, second is evening prayer, dhuha prayer fasting Monday Thursday, study and qurban. The three teachers have exemplified good attitudes in applying Humanism and Religious values based on observations and field findings.